Lairage time effect on meat quality in Hereford steers in rangeland conditions - Costa, Franciely de Oliveira [UNESP]; Brito, Gustavo; Manuel Soares de Lima, Juan; Sant'Anna, Aline Cristina [UNESP]; Rodrigues Paranhos da Costa, Mateus Jose [UNESP]; del Campo, Marcia (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2019)
This study evaluated lairage time effects on carcass and meat quality traits of Hereford steers. Thirty Hereford steers fed on pasture were assigned to two treatments according to lairage time: 3 h (n = 15) and 12 h (n = 15). Individual temperament was assessed using crush score and flight speed. pH decline, glycogen content, meat color, and shear force were measured. pH was not different between treatments at any time point, showing a normal decline rate. Meat color and shear force did not differ between treatments, but muscle glycogen was lower in treatment with 3 h, not enough to affect quality but suggesting a higher level of stress in 3 h lairage time. Temperament did not have any impact on carcass and meat quality traits. No differences were found in pH, color, and tenderness between treatments, but the lower muscle glycogen concentrations for the shorter lairage suggest a higher risk regarding meat quality.
Keywords: crush score; flight speed; glycogen; pH; shear force